Wireless localization and position tracking in urban built-up environments - Lin, Peter Zhao Yuan. (2012)
This report evaluate on the study of the channel parameters, the recommend channel models and ranging techniques, the channel measurements in the frequency domain of 2GHz to 3GHz will carry out on the laboratory. This measurement campaign consists of collecting channel transfer functions at the laboratory to stimulate the Line of sight configuration. But before the experiment is implemented, the transmitter and the receiver is been replace by the bi-conical antenna. The testing of antenna is conducted by measuring its return power loss and the radiation pattern by applying the theory of S parameter and the Polarization respectively. The purpose of the Line of Sight experiment also includes the collective data which is constructed by the time domain response and the power delay profiles of the channels. Channel Parameters like RMS delay spread, path loss exponent are also been studied and the distribution function that describe the amplitudes of multipath arrivals.